Integrating in situ formation of nanozymes with mesoporous polydopamine for combined chemo, photothermal and hypoxia-overcoming photodynamic therapy. Issue 98 (22nd November 2019) - Hu, Xiaochun; Lu, Yonglin; Shi, Xiaoke; Yao, Tianming; Dong, Chunyan; Shi, Shuo
Abstract : A multi-functional nanoplatform (M-Pt-BCD) for combined chemo, photothermal and hypoxia-overcoming photodynamic therapy is described. Abstract : Based on the Pt nanozyme modified mesoporous polydopamine in situ, a multi-functional nanoplatform was established, which could overcome tumour hypoxia by catalyzing overexpressed H2 O2 in tumour cells to enhance photodynamic therapy. In vivo results confirmed that the tumour growth was inhibited efficiently by synergetic therapy.